Interrelationships of Polydolopidae (Mammalia: Marsupialia) from South America and Antarctica - Chornogubsky Clerici, Laura (Zoological Journal of the Linnean Society)
Polydolopidae is a family of Palaeogene marsupials recorded from outcrops in southern South America and the Antarctic Peninsula. They are mostly represented by skull fragments or maxillary, dentary and molar remains. A taxonomic and systematic revision is carried out with the inclusion of a phylogenetic analysis encompassing almost every polydolopid species and five marsupial species found to be related to them in previous analyses (Bonapartherium hinakusijum, Epidolops ameghinoi, Microbiotherium tehuelchum, Prepidolops didelphoides and Roberthoffstetteria nationalgeographica). The Polydolopidae was recovered as a monophyletic group, even thoughno resolution about its sister-group can be found. The following genera are recovered: Antarctodolops, Amphidolops, Archaeodolops, Eudolops, Hypodolops gen. nov., Kramadolops, Pliodolops, Pseudolops and two unidentified genera (Gen. et sp. indet 1 and 2). One genus and three new species are recognized. The family appeared at the beginning of the Palaeocene and disappeared during the Early Oligocene. The extinction of the group could be related to climaticdeterioration in the Early Oligocene, when temperature and the humidity dropped, provoking desertification in the region where Polydolopids evolved. Fil: Chornogubsky Clerici, Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina